A Design Anthropology Critique of Active Aging as Ageism - Linda Tonolli; Maurizio Teli; Vincenzo D’Andrea (Interaction Design and Architecture(s), 2015)
This paper proposes a design anthropology critique of active aging as ageism in the design of information technologies for seniors. With ageism we refer to narratives coalesced around the label “active aging” in European policies and system design that focus on seniors as a homogeneous group of people in need of help. We discuss the findings of two empirical participatory design projects we have been dealing with: 1) a bottom-up senior organization in a small village in a mountain area and 2) a series of workshops organized with seniors in an urban area. In both cases, the relations between the anthropologist and the people involved, prompted reflexive moments that brought anthropological relocations of the designers' perspective. In conclusion, we stress how such relocations could benefit participatory designs through the concept of design by subtraction and the adoption of a feminist perspective.